The Impact of Pasir Putih Beach’s Tourism, Situbondo, on Job and Business Opportunities - Muthahharah, Afiefah; Adiwibowo, Soeryo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
The objective of this research is to analyze the impact of Pasir Putih Beach’s tourisms on job and business opportunities. The results show that, first, tourism at Pasir Butih Beach strongly promote job and business opportunities for local i.e. hotel and homestay, boat rental, restaurants, peddlers, retailers, and packman. Second, with regards to full job in tourism sector, the economic contribution of tourism to total household income is quite significant. The average monthly income of the rental boatman could reach 69.3 percent (or Rp 859 700) of the total monthly income. Meanwhile for the peddler the contribution of tourism sector to the total household income reach 73.1 percent (or Rp 544 400). As for merchandise, the contribution from tourism reaches 50.3 percent (or Rp 455 500) out of the total household income.Keyword: tourism, job opportunity, business opportunity, and household income